Record of ocellated shrimp goby, Tomiyamichthys russus (Actinopterygii: Perciformes: Gobiidae), from the Andaman Islands, India - J. Praveenraj; P.T. Rajan; R. Kiruba-Sankar; S. Dam Roy (Acta Ichthyologica et Piscatoria, 2017)
The ocellated shrimp goby, Tomiyamichthys russus (Cantor, 1849), is reported for the first time from the Andaman Islands, India based on a single, female specimen collected during a shore seine operation at Port Blair, South Andaman. The examined specimen is described taking into account the meristics, morphometry, sensory pore arrangement, and the papillae pattern. This finding constitutes the first report of the genus Tomiyamichthys from the Andaman Sea, with a range extension towards Andaman coast. Plain.